Perlindungan Data Pribadi Dalam Kejahatan Transnasional Lintas-Negara - Ferina Putri Wulandari; Andi Aina Ilmih (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Protection of personal data in the context of transnational crime across borders is becoming increasingly important in the current digital era. Rapidly developing information and communication technologies have brought great benefits in global information exchange, but also brought serious risks to the security of individual data. This research aims to investigate the influence of developments in information and communication technology on personal data protection in facing the threat of transnational crime, explore the challenges faced, and identify strategies and the influence of international cooperation in increasing the effectiveness of personal data protection. The research method used is literature study, with analysis of relevant information from various sources.